Pengaruh Persepsi Harga dan Word of Mouth terhadap Kepuasan Pelanggan melalui Keputusan Pembelian - Mutiara Aprilia; Rivera Pantro Sukma (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aimed to analyze the influence of price perception and WOM on customer satisfaction through purchasing decisions at FamilyMart Gran Rubina. Data were collected through the distribution of questionnaires to 200 respondents, using accidental sampling and the data were analyzed using Structural Equation Modeling (SEM) through PLS version 3.0 software. The results showed that price perception significantly influenced customer satisfaction, price perception significantly influenced purchasing decisions, WOM significantly influenced customer satisfaction, WOM significantly influenced purchasing decisions, and purchasing decisions also had a direct and significant influence on customer satisfaction. The indirect effects of price perception on customer satisfaction through purchasing decisions were found to be positive, as well as the indirect effects of WOM on customer satisfaction through purchasing decisions were found to be positive.